Identification of BMP2 gene and its association with growth traits in the razor clam Sinonovacula constricta - Xiaojie Zhu; Jiaxi Zhao; Congying Lai; Liyuan Lv; Hanhan Yao; Yinghui Dong (Aquaculture Reports, 2023)
Growth is a crucial and intricate trait that significantly impacts clam breeding. BMP2, a member of the bone morphogenetic protein family, is widely recognized for its vital role in promoting growth and development. To study the possible functions of BMP2 in the razor clam Sinonovacula constricta, Sc-BMP2 was identified and characterized from S. constricta genome, and its correlations with growth traits were also analyzed. Compared with Sc-BMP3, Sc-BMP7 and Sc-BMP10, Sc-BMP2 had higher homology in the vertebrates and mollusks. The Sc-BMP2 highly conserved and exhibited an N-terminal signal peptide, Arg-X-X-Arg site and seven conserved cysteine. The results of tissue expression showed that Sc-BMP2 was expressed much higher in the mantle and foot (P < 0.05), while extremely low expression was found in the hepatopancreas. In the early development stages, the expression level of Sc-BMP2 gradually increased, reaching notably elevated levels in D-shaped larvae compared with other development stages (P < 0.01). After inhibition of Sc-BMP2 expression using RNA interference (RNAi) technology, the expression levels of Sc-Chsy1 increased significantly in the central zone of mantle (P < 0.05), indicating Sc-Chsy1 was regulated by Sc-BMP2 during shell formation. Further, two single nucleotide polymorphisms (SNPs) loci (g.2287 and g.2243) were screened out in the 3′ UTR region of the Sc-BMP2 gene and verified to be significantly correlated with growth traits using 226 individuals from two populations. In conclusion, the results indicated that Sc-BMP2 was a growth related gene, and the identified SNP loci provide growth-related markers for molecular marker-assisted breeding of the clam.